Protective Effect of Nicotine on Sepsis-Induced Oxidative Multiorgan Damage: Role of Neutrophils - YEGEN, BERRAK; ÖZBEYLİ, DİLEK; ERCAN, FERİHA; ÖZDEMİR KUMRAL, ZARİFE NİGAR (OXFORD UNIV PRESS, 2017)
Despite its adverse health consequences, tobacco smoking is associated with lower incidence of several neurodegenerative and inflammatory diseases. The present study is aimed to show the effects of nicotine, major tobacco constituent, on five organs targeted by sepsis. Male Wistar albino rats received tap water with (5mg/kg) or without nicotine for 14 days. Under ketamine anesthesia, sepsis (n = 50) was induced by ligation and puncture of the cecum, while sham group (n = 8) had only laparotomy. In other rats, nicotine drink was withdrawn for 5 days before sepsis induction, while in acute nicotine group, rats were injected with nicotine (30mg/kg, i.p.) before sepsis, but had no oral intake. Rats were decapitated 24 hours after surgery to obtain lung, liver, ileum, heart, and kidney tissues to determine malondialdehyde (MDA) and glutathione (GSH) levels and myeloperoxidase (MPO) activities. Data were analyzed by one-way analysis of variance and Tukey multiple comparison tests or Student's t test. Chronic nicotine administration or its withdrawal reduced lipid peroxidation and MPO activity and prevented GSH depletion with some varying results in different target tissues. Nicotine injection prior to sepsis depressed MPO activity in all tissues and reduced MDA levels except for the lung, while GSH levels were elevated only in the hepatic and ileal tissues. Histologically observed injury was ameliorated by all nicotine treatments at varying degrees. The findings of the present study indicate that long-term nicotine administration reduces sepsis-induced oxidative damage in several tissues, which appears to involve inhibition of neutrophil activity in the inflamed tissues. Nicotine administration or its withdrawal reduced lipid peroxidation and neutrophil content and prevented GSH depletion with some varying results in different target tissues. A single injection prior to sepsis induction depressed MPO activity in all the tissues and reduced all tissue MDA levels except for the lung. When nicotine was withdrawn for 5 days, its inhibitory effect on MPO activity was still present in all the tissues except for the liver. Microscopically an improved inflammatory response was observed in all the tissues of rats that have received different nicotine pretreatment regimens.
Keywords: ORGAN INJURY; RAT MODEL; SMOKING; INFLAMMATION; EXPOSURE; ACTIVATION; MORTALITY; SURVIVAL; COLITIS; DISEASE